DAMPAK CSR STRENGTHS DAN CSR CONCERNS PADA KINERJA PERUSAHAAN MANUFAKTUR DI INDONESIA - Ananda Debby Pratami; Agung Juliarto (Diponegoro Journal of Accounting, 2020)
This research is to examine the impact of CSR Strengths and CSR Concerns on the performance of manufacturing companies in Indonesia. In addition, this study also examines the effect of CSR performance (CSR Strengths and CSR Concerns) on financial performance if the company operates internationally. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017 and included in the Main Board Index. The sample selection uses purposive sampling method to obtain 58 companies. Multiple linear regression analysis is used to test the hypotheses. The results show that CSR Strengths has a positive effect on financial performance and CSR Concerns has a negative effect on financial performance. However, the results indicate that international operations do not strengthen the positive influence of